Multifractal analysis of textured silicon surfaces - Jurečka, Stanislav; Angermann, Heike; Kobayashi, Hikaru; Takahashi, Masao; Pinčík, Emil (Applied surface science, 2014)
•We prepared pyramidal textures at Si with different shape distributions.•The texture morphology properties were examined by statistical and fractal methods based on the AFM images.•Optical properties were studied by the spectral reflectance in 3D arrangement.•General fractal dimension, multifractal singularity spectra and probability distribution of fractal dimension are very sensitive to small changes in the real texture.•Fractal properties significantly influence the optical properties of textured Si surface. Pyramidal textures with random distribution of texture shapes on crystalline Si wafers substantially reduce reflection losses of substrates for high-efficiency solar cells, detectors and similar applications. In this work random pyramids on n-type Si wafers were prepared by anisotropic surface etching in potassium hydroxide (KOH) solution. The morphology of pyramidal shapes was examined by the AFM method and reveals high complexity of the surface structure. Properties of AFM observed pyramidal textures were characterized by the statistical and multifractal methods. This approach provides good platform for the distinguishing between fine details in the pyramidal distributions. Significant correlation between the fractal properties of surface texture and its optical properties characterized by the spectral reflectance function is observed.